The inequality in the systems of contracting in the public administration inside the colombian condition (2013)
he present article of reflection appears in order to be able to show a more critical and realistic perspective brings over of the labor panorama that is lived nowadays in the country, as for the inequality in the different systems of contracting that uses the public administration and his socioeconomic incident inside the Colombian State. For which Law seeks to analyze and to understand the structure of the General Statute of Public Contracting in Colombia - 80/93. In order to establish the consequences of the application of the different ways of contracting personal services by means of the juridical figure of the Contract of Provision of services, situation that favors the creation of parallel lists, tercerización and intermediation of the services, the creation of temporary, such as supernumerary, provisional employments of plant, orders, between other modalities that they contribute with the deterioration of the working conditions and the reduction of guarantees, generating uncertainty and labor instability.